2014
DOI: 10.1016/j.str.2013.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Prion Models Based on Comprehensive Mutation Data of Mouse PrP

Abstract: The structural details of the essential entity of prion disease, fibril prion protein (PrP(Sc)), are still elusive despite the large body of evidence supporting the prion hypothesis. Five major working models of PrP(Sc) structure, which are not compatible with each other, have been proposed. However, no systematic evaluation has been performed on those models. We devised a method that combined systematic point mutation with threading on knowledge-based amino acid potentials. A comprehensive mutation experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…Recent studies, including ours, showed that prion conversion tolerates a certain level of sequence changes at the junction of PrP helices H2 and H3, suggesting that this region might be less essential (10,(34)(35)(36)(37). We show here that a deletion of a stretch of residues forming the C terminus of helix H2 of PrP C is plainly compatible with prion conversion and transfer of strain properties.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Recent studies, including ours, showed that prion conversion tolerates a certain level of sequence changes at the junction of PrP helices H2 and H3, suggesting that this region might be less essential (10,(34)(35)(36)(37). We show here that a deletion of a stretch of residues forming the C terminus of helix H2 of PrP C is plainly compatible with prion conversion and transfer of strain properties.…”
supporting
confidence: 52%
“…We propose instead that the 193-197 area, which is alpha-helical in PrP C , is converted into an element that might be less critical for PrP Sc structure, i.e., an unstructured loop segment. This is also supported by different observations: the region tolerates insertion of unrelated heptapeptide or octapeptide (34,36) or replacement of one of the four threonines by a cysteine (10) and also individual replacement of each amino acids by any other one (37); this region is also significantly more accessible to deuterium exchange than surrounding areas (4); and, finally, in the particular example of the HETs prion of Podospora anserina whose structure is resolved, a series of short deletions was performed, and the only ones compatible with prion conversion were found to localize in the loop connecting the two stacked rings of beta strands forming the amyloid fiber (67). Therefore, our results are incompatible with PrP Sc models including residues 193 to 197 into a beta strand (11,68).…”
Section: Discussionmentioning
confidence: 59%
“…One fibril model of the HET-s peptide (37) and insulin (32) and two models of PrP fibrils (38,39) were stretched along the fibril axis, which allows determination of the modulus and strength from stress-strain curves (Figs. 3 A and S11 A).…”
Section: Correlation Between Nanomechanics and H-bond Densitiesmentioning
confidence: 99%
“…Currently, there are no curative treatments for AD and other prion diseases, and also the underlying mechanism had not been fully elucidated (Karamanos et al, 2015, Visanji et al, 2013, Wisniewski and Drummond, 2016. On the other hand, there were no appropriate animal models or limited animal models for the drug development research (Fernandez-Borges et al, 2013, Ghate et al, 2014, Shirai et al, 2014. In the last 20 years, several mouse models had been established and were used in a number of research fields of prion diseases, including pathology (Corda et al, 2015, Ghate et al, 2014 and genetics (Asante et al, 2015, Friedman-Levi et al, 2011.…”
Section: Prnp Polymorphisms In Six Mouse Strainsmentioning
confidence: 99%
“…An important limitation was the existence of appropriate models of the disease (Fernandez-Borges et al, 2013). In order to study the molecular mechanism of the prion diseases and to test the drugs, many mouse models had been established and they are required (Asante et al, 2015, Bajsarowicz et al, 2012, Bruce et al, 2002, FernandezBorges et al, 2015, Friedman-Levi et al, 2011, Lee et al, 2013, Morales et al, 2015, Shirai et al, 2014. Among these mouse models, there included a number of transgenic models which are expensive, with short life, clinical symptoms and genetic instability, and other associated problems.…”
Section: Prnp Polymorphisms In Six Mouse Strainsmentioning
confidence: 99%